Penggunaan Pupuk Hayati Dan Pupuk Npk Untuk Menekan Penyakit Layu Dan Meningkatkan Pertumbuhan Dan Hasil Tanaman Kacang Panjang (Vigna sinencis L.) - A. Marthin Kalay; Aneke F Langoi; Abraham Talahaturuson; Suman Sangadji; Louisa S Manuhutu (Agrologia, 2017)
The use of either liquid or carrier-based biofertilizers reduced the application of excessive inorganic fertilizers. The purpose of this research was to verified the effect of biofertilizer application of Bokelas Plus (BP) and NPK inorganic fertilizer on the intensity of dumping off diseases, growth and yield of long bean plants. The experiment have been done in experimental field of Agricultural Extension Center of Baguala Sub-district in Nania Village, Ambon city. The treatments were 400 kg NPK / ha, 300 kg NPK / ha, 200 kg NPK / ha, 75 kg BP / ha + 400 kg NPK / Ha, 75 kg BP / ha + 300 kg NPK / ha, and 75 kg BP / ha + 200 kg NPK / ha. The results showed that the application of biofertilizer BP and NPK fertilizer affected intensity of wilt disease caused by Scerotium rolfsii pathogen, plant height, long and pea pod weight. The best dose was 75 kg BP / ha + 300 kg NPK / ha. This experiment suggest that BP biofertilizer reduced the use of NPK fertilizer by 25%.